Retention of autism spectrum disorder diagnosis: The role of co-occurring conditions in males and females. (May 2016) - Wu, Yen-Tzu; Maenner, Matthew J.; Wiggins, Lisa D.; Rice, Catherine E.; Bradley, Catherine C.; Lopez, Maya L.; Kirby, Russell S.; Lee, Li-Ching
Highlights: 91% of males and females with ASD diagnosis retained their ASD diagnosis. Co-occurring intellectual disability and sensory integration disorder were associated with diagnosis change from ASD to non-ASD in males. Delays in personal/social development and epilepsy were associated with diagnosis change from ASD to non-ASD in females. More ASD-related evaluations and less ASD-related impairment were associated with ASD being ruled out in both sexes. Abstract: This study examined associations between ASD diagnosis retention and non-ASD co-occurring conditions (CoCs) by child sex. The sample included 7077 males and 1487 females who had an ASD diagnosis documented in their school or health records in a population-based ASD surveillance system for 8-year-old children. ASD diagnosis retention status was determined when an initial ASD diagnosis was not later ruled out by a community professional. We found that ASD diagnosis remains fairly stable, with only 9% of children who had an initial documented ASD diagnosis later being ruled-out. Although most of the associations between the ASD diagnosis retention status and CoCs are similar in both sexes, the co-occurrence of developmental diagnoses (e.g., intellectual disability or sensory integration disorder) was predictive of ASD diagnostic changes in males, whereas the co-occurrence of specific developmental (e.g., personal/social delay) and neurological diagnosis (e.g., epilepsy) was associated with ASD diagnostic change in females. More ASD-related evaluations and less ASD-related impairment were associated with later ASD rule outs in both sexes. Our findings highlight that CoCs can complicate the diagnostic picture and lead to an increased likelihood of ambiguity in ASD diagnosis. Using sensitive and appropriate measures in clinical practice is necessary for differential diagnosis, particularly when there are co-occurring developmental conditions.